2017
DOI: 10.3892/ijo.2017.4070
|View full text |Cite
|
Sign up to set email alerts
|

Malformin A1 treatment alters invasive and oncogenic phenotypes of human colorectal cancer cells through stimulation of the p38 signaling pathway

Abstract: Malformin A1 (MA1), a cyclic pentapeptide isolated from Aspergillus niger, has been found to possess a range of bioactive properties including antibacterial activity. However, it is unclear whether MA1 exerts an anticancer effect or not. In this study, we conducted in vitro experiments to investigate its anticancer properties in human colorectal cancer cells. The effect of MA1 on human colorectal cancer cells, SW480 and DKO1, was examined by the WST-1 cell viability assay, inverted microscopy, 5-bromo-2-deoxyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, malformins have never been detected after mycotoxicosis caused by A. niger . Malformins are very promising anti-cancer agents, however (Park et al 2017b ).…”
Section: Secondary Metabolite Potentialmentioning
confidence: 99%
“…Furthermore, malformins have never been detected after mycotoxicosis caused by A. niger . Malformins are very promising anti-cancer agents, however (Park et al 2017b ).…”
Section: Secondary Metabolite Potentialmentioning
confidence: 99%
“…For instance, Park et al. (2017) investigated the cytotoxicity of malformin A1 (MA1), a cyclic pentapeptide from Aspergillus niger. And it has been found that MA1 displays potent cytotoxicity toward various cancer cell lines.…”
Section: Function and Bioactive Mechanism Of Mdcpsmentioning
confidence: 99%
“…Cyclic peptides are cyclic compounds formed by either proteinogenic or nonproteinogenic amino acids along with the amide bonds between them (Xiaohan et al, 2017). Currently, cyclic peptides have been found in various sources, including plants (de Veer et al, 2019), mammals (Falanga et al, 2017), fungi (Bilal et al, 2018;Liang et al, 2017;Liddicoat & Lavelle, 2019;Park et al, 2017), bacteria (Karanam et al, 2020;Li et al, 2020;Ling et al, 2015;Wang et al, 2022), and actinomycetes (Byun et al, 2020;Jiang et al, 2021;Nalli et al, 2017;Shin et al, 2018;Song et al, 2019). Cyclic peptides overcome most of the disadvantages of their linear counterparts and exhibit higher F I G U R E 1 Overview of synthesis, biological mechanisms, and food safety applications in microorganism-derived cyclic peptides metabolic stability, membrane permeability, and oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stimulation of the AMP-activated serine/threonine protein kinase/mammalian target-of-rapamycin (AMPK/mTOR) pathway by adding oxidative stress or decreasing ATP could lead to MA 1 -mediated autophagy [299]. In human colorectal cancer cells (SW480 and DKO1), invasive and oncogenic phenotypes were modified through p38 signaling pathway [300]. Recently, the marine-derived fungus A. tubingenesis also yielded MA 1 with significant cytotoxicity against HeLa (IC 50 = 9.48 nM) and P388 (IC 50 = 132.9 nM) cell lines [301].…”
Section: Anticancer Cyclopeptides Derived From Non-marine Fungimentioning
confidence: 99%